Washback of the ICFES Exam: A Case Study of Two Schools in the Departamento del Atlántico. - Barletta, Norma; May, Ofelia (Íkala, Revista de Lenguaje y Cultura, 2006)
This study explores the impact of the compulsory state examinations at the end of secondary schooling (the ICFES exams) on English teaching practices in Colombia, since these examinations were modified in 2000. More specifically, we describe the washback effect of the English Test in two public schools. The washback effect is discussed, and results presented that were obtained through the triangulation of information and sources. Received: 28-03-06 / Accepted: 31-07-06 How to reference this article: Barletta, N & May, O. (2006). Washback of the ICFES Exam: A Case Study of Two Schools in the Departamento del Atlántico. Íkala. 11(1), pp. 235 – 261